Motivasi Mahasiswa SST Fisioterapi dalam Belajar Bahasa Inggris - Noerdjanah, Noerdjanah; Khomarun, Khomarun (Jurnal Terapi Wicara dan Bahasa, 2025)
Background: English plays a crucial role in education and professional life, including in physiotherapy, as most scientific literature and other sources of knowledge are written in it. However, students of the Physiotherapy Specialization Program (SST) at the Ministry of Health Polytechnic of Surakarta still exhibit low learning motivation, which results in suboptimal English learning achievement. Objectives: This study aims to analyze the relationship between learning motivation and English learning achievement of physiotherapy students. Methods: The study used a quantitative correlational design with a cross-sectional approach, involving 300 respondents selected using a total sampling technique. The research instrument was a learning motivation questionnaire that had been tested for validity and reliability (r count > 0.113; Cronbach's Alpha = 0.966). Data were analyzed using the Pearson Product Moment correlation test after meeting the assumptions of normality and linearity. Results: The results showed a positive and significant relationship between learning motivation and English learning achievement (r = 0.661; p < 0.01), with an effective contribution of 43.7%. This means that the higher a student's learning motivation, the higher their English learning achievement. Conclusion: Learning motivation plays a crucial role in determining the academic success of physiotherapy students. The results of this study are expected to serve as a basis for developing learning strategies that can foster learning motivation and improve the quality of English language learning in vocational health education settings. Keywords: Motivation, Learning Achievement, English